Glucagon-like peptide 1 receptor agonist and reduced liver and non-liver complications in adults with type 2 diabetes and metabolic dysfunction-associated steatotic liver disease: a target trial emulation study - Xianhua Mao; Xinrong Zhang; Rongtao Lai; Ka-Shing Cheung; Man-Fung Yuen; Ramsey Cheung; Wai-Kay Seto; Mindie H. Nguyen (Clinical and Molecular Hepatology)
Background/Aims Information about the association of glucagon-like peptide-1 receptor (GLP-1RA) with liver and non-liver complications is insufficient in patients with type 2 diabetes (T2D) and metabolic dysfunction-associated steatotic liver disease (MASLD). We conducted a target trial emulation study to evaluate whether GLP-1RA decreases the risk of liver and non-liver outcomes. Methods Patients with T2D and MASLD initiating GLP-1RA or dipeptidyl peptidase-4 inhibitor (DPP-4i) were included from 2013 to 2022 in Merative™ Marketscan® Research Databases. Primary outcomes included incidences of (1) hepatocellular carcinoma (HCC) and cirrhosis, and (2) cardiovascular disease (CVD), chronic kidney disease (CKD), and non-liver cancer. Inverse probability of treatment weighting was applied to balance baseline characteristics and Cox regression models were conducted to estimate hazard ratio (HR) and 95% confidence interval (CI). Results In the intention-to-treat design, GLP-1RA, compared with DPP-4i, had a significantly lower incidence (per 1,000 person-years) of HCC (0.8 vs. 1.7; HR 0.53, 95% CI 0.39–0.71), of cirrhosis (29.3 vs. 32.9; HR 0.91, 95% CI 0.86–0.96), of CVD (57.2 vs. 73.9; HR 0.90, 95% CI 0.86–0.95), of CKD (4.5 vs. 6.8; HR 0.73, 95% CI 0.64–0.84), and of non-liver cancer (16.9 vs. 22.9; HR 0.82, 95% CI 0.77–0.89). In the per-protocol design, significant inverse associations for these study outcomes still were observed, with HR 0.60–0.77. Conclusions In this emulated target trial of nationwide patients with T2D and MASLD, GLP-1RA use, when compared with DPP-4i, was associated with a significantly lower risk of liver and non-liver complications.